ACCESS TO POSBAKUM IN PANDEMIC TIMES AND THE DIGITAL ERA FOR THE COMMUNITY AS A MEANING OF SOCIAL JUSTICE FULFILLMENT - Albana, Muhamad Zaky; Alfi Syahr, Zulfia Hanum (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Access to justice for the community is a mandate from the Constitution Article 28 Paragraph 1, which states that everyone has the right to recognition, guarantees, protection, fair legal certainty, and equal treatment before the law. The development of access to posbakum is a form of fulfilling social justice for the community following the mandate of the fifth principle of Pancasila. It is also stated in Law Number 48 of 2009 concerning Judicial Power, which requires the court to assist justice seekers, try to overcome all obstacles, and achieve a simple trial, fast and low cost. Therefore, a legal aid post (Posbakum) is established at every court to help the underprivileged gain access to justice and equality before the law. So far, posbakum can only be accessed by going to court directly, so during the Covid-19 pandemic, people were hampered from getting these services. Especially for people who live in villages far from the courts, it is tough for them to access and obtain legal aid services from the courts. This paper examines how to develop posbakum so that village communities can more easily access it. It will also investigate the obstacles people in rural areas face in obtaining posbakum services. The method used is qualitative with data collection techniques through library research and interviews, coupled with a normative study of related regulations. This study shows that the existence of Posbakum, through partnerships with the village government, can provide better access to justice for village communities.